Recent Study on Heat Transfer Characteristics of Staggered Inclined Discrete Ribs with Combined Gap Arrangement - M. K. Solanki; K. R. Aharwal (Newest Updates in Physical Science Research Vol. 1, 2021)
Artificial roughnesses in the form of ribs are an advantageous technique to increase solar air heaters’ warmth efficiency. This research work presents new roughness utilized in a roughened channel and assesses the effective efficiency for a gap of inclined discrete rib with staggered connection geometry. A strong system for enhancing the heat transfer between the roughened plate and the working fluid is the use of artificial geometry on the absorber roughened surface. The present new roughness geometry has parameters such as roughness pitch of rib of 8.0, attack angle of 75°, gap positions are varied between 0.3 & 0.1 – 0.3 & 0.4, aspect proportion of 8.0, rib height of 0.045 and rib gap width of 1.0. The Reynolds number range of 3000-14000. The maximum improvement coefficient of friction (ƒ) and Nusselt Number (Nu) is achieved as 3.43 and 3.03 respectively, compared to the smooth channel. For the combined gap position of 0.3 & 0.3, a higher THP is achieved.